Submanifolds of Euclidean space with parallel mean curvature vector - Tahsin Ghazal; Sharief Deshmukh (International Journal of Mathematics and Mathematical Sciences)
The object of the paper is to study some compact submanifolds in the Euclidean space Rn whose mean curvature vector is parallel in the normal bundle. First we prove that there does not exist an n-dimensional compact simply connected totally real submanifold in R2n whose mean curvature vector is parallel. Then we show that the n-dimensional compact totally real submanifolds of constant curvature and parallel mean curvature in R2n are flat. Finally we show that compact Positively curved submanifolds in Rn with parallel mean curvature vector are homology spheres. The last result in particular for even dimensional submanifolds implies that their Euler poincaré characteristic class is positive, which for the class of compact positively curved submanifolds admiting isometric immersion with parallel mean curvature vector in Rn, answers the problem of Chern and Hopf